Association of hemoglobin levels with metabolic traits in women with PCOS - Nikke Virtanen; Emilia Pesonen; Ulla Saarela; Elisa Hurskainen; Riikka K. Arffman; Peppi Koivunen; Terhi Piltonen (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Within normal variation, higher hemoglobin (Hb) levels are associated with poorer metabolic profile in population cohorts, underlying the link between oxygen delivery and cell metabolism. Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among women and is commonly accompanied by metabolic derangements. In this study we sought to investigate Hb levels, and their metabolic associations, in women with PCOS. Material and Methods We used data from Northern Finland Birth Cohort 1966 to evaluate Hb levels in women with or without PCOS at the ages of 31 and 46 years. Linear regression models were used to investigate associations between Hb levels and essential metabolic parameters in both groups. Results Women with PCOS had higher Hb levels than controls at the age of 31 years but not at the age of 46 years. Hb levels were associated positively with most of the metabolic parameters tested (body mass index, waist circumference, fasting insulin, homeostatic model assessment–insulin resistance (HOMA‐IR), blood pressure, inflammatory markers, and blood lipids), with stronger associations in women with PCOS than in non‐PCOS controls. There were fewer associations at the age of 46 than at 31 years, and body mass index seemed to explain many, though not all, differences between the PCOS and non‐PCOS groups. Conclusions Women with PCOS have higher Hb levels at the age of 31 years. In both women with and without PCOS, Hb levels associate with poorer metabolic profile.